Two Tightly Linked Genes for Soybean Mosaic Virus Resistance in Soybean. Issue 4 (5th May 2017) - Klepadlo, Mariola; Chen, Pengyin; Shi, Ainong; Mason, R. Esten; Korth, Kenneth L.; Srivastava, Vibha; Wu, Chengjun
Abstract : Soybean mosaic virus (SMV), a member of the Potyviridae family, is the most common virus negatively affecting yield and seed quality in soybean [ Glycine max (L.) Merr.]. Seven SMV strains, G1 through G7, and three independent SMV resistance genes ( R ‐genes), Rsv1, Rsv3, and Rsv4, have been previously identified. The Rsv1 locus contains at least 10 alleles conferring differential plant reactions to SMV strains, and it was mapped at very complex resistance‐gene‐rich region. In this study, two alleles of the Rsv1 locus were analyzed by crossing PI 96983 ( Rsv1 ) and cultivar York ( Rsv1‐y ) soybean to evaluate whether Rsv1 and Rsv1‐y belong to the same or different but closely linked loci. To break possible linkage, 3000 F2:3 lines were developed and investigated using infections of the SMV‐G1 strain in a greenhouse. The occurrence of segregating and susceptible lines indicated tight linkage between two genes. The recombination frequency (RF) was estimated using the maximum likelihood (ML) formula concluding that Rsv1 and Rsv1‐y are two tightly linked loci located apart with genetic distance of 2.2 cM on chromosome 13. A new symbol of Rsv5 has been assigned for the resistance gene in York to replace the original Rsv1‐y allele assignment. This research provided the first evidence for existence of two R ‐genes on chromosome 13, conferring resistance to different SMV strains. Both loci, Rsv1 and Rsv5, can be easily transferred into susceptible cultivars in a breeding program to provide broad and durable protection against SMV strains.